Fast breakthrough of resistant cytomegalovirus during secondary letermovir prophylaxis in a hematopoietic stem cell transplant recipient - Susanne Jung; Manuela Michel; Thomas Stamminger; Detlef Michel (BMC Infectious Diseases, 2019)
Abstract Background The compound letermovir (LMV) has recently been approved for the prophylaxis of cytomegalovirus (CMV) infection and disease in adult CMV seropositive recipients of an allogeneic hematopoietic stem cell transplant. LMV inhibits CMV replication by binding to the viral terminase complex. However, first cases of clinical LMV resistance have been occurred. Here we report a fast breakthrough of resistant cytomegalovirus during secondary LMV prophylaxis in a hematopoietic-cell transplant recipient. Case presentation A 44-year-old male patient with acute myeloid leukemia (AML) experienced a CMV-reactivation within the first 4 weeks of allogeneic hematopoietic-cell transplantation. Administration of LMV was initiated at day + 34. Due to increasing viral loads, LMV treatment was discontinued after 8 days. The patient was then administered with valganciclovir (valGCV) until viral DNA was undetectable. Due to neutropenia, valGCV treatment was switched to LMV secondary prophylaxis. For 4 weeks, the patient maintain virologic suppression. Then, CMV viral loads increased with a fast kinetic. Genotypic testing of the viral polymerase UL54, the kinase UL97 as well as the viral terminase UL56 and UL89 revealed the mutation C325Y in UL56, which is associated with the high level LMV resistance. Conclusion It is known that Letermovir is approved for prophylactic purposes. However, it may be used for some patients with CMV infection who either have failed prior therapies or are unable to tolerate other anti-CMV compounds. Particularly, the administration of LMV should be avoided in patients with detectable viral loads. When this is not possible, viral load must be routinely monitored along with UL56 genotyping. Furthermore, LMV administration at high virus loads may foster the rapid selection of resistant CMV mutants.